A new set of quantitative trait loci linked to lipid content in Coffea arabica - Muniz, Herison Victor Lima; Ariyoshi, Caroline; Ferreira, Rafaelle Vecchia; Felicio, Mariane Silva [UNESP]; Pereira, Luiz Filipe Protasio (FapUNIFESP (SciELO), 2024)
Lipids are compounds that play an important role in coffee bean development, contributing to beverage quality. Genome-wide association studies (GWAS) were conducted to pinpoint quantitative trait nucleotides (QTNs) linked to lipid metabolism in Coffea arabica. Genotyping by sequencing (GBS) and phenotyping data from 104 wild C. arabica accessions, Mundo Novo cultivar, and C. arabica var. Typica were utilized. GBS data were aligned to C. arabica Et039 reference genome, and both single-locus and multi-locus GWAS methods were employed. Methods were adjusted for kinship matrix, population structure, and principal component analysis. Of the 19 QTNs identified, 5 showed consistency across different population structure adjustments. The multi-locus methods mrMLM and FarmCPU proved more effective in identifying QTNs associated with lipid content. Four QTNs were situated near seven genes potentially involved in lipid metabolism. Higher frequencies of identified QTNs in accessions with elevated lipid content suggest their utility as markers for coffee plant breeding.
Keywords: Allotetraploid; coffee; GWAS; SNP markers